Marketing Strategy Analysis(Case Study: Ambit Village UMKM (Bangreng Crackers)) - Kurniasih, Nining; Sopyan, Anggi Taufik; Nurzaeti, Diesta Dwi; Wulan, Fazra Raisha; Purwanasari , Sri Nuraini (SINTESA, 2024)
This study aims to analyze the marketing strategies of UMKM Kerupuk Bangreng Sawargi in Village Ambit, Kecamatan Situraja, Kabupaten Sumedang. Using a descriptive qualitative approach, data were collected through observations, semi-structured interviews, and documentation. SWOT analysis was employed to identify internal strengths and weaknesses as well as external opportunities and threats. The findings reveal that the business’s main strengths lie in its authentic taste and competitive pricing, while weaknesses include reliance on traditional marketing methods and limited capital. Opportunities such as government support programs and the growth of digital markets can be leveraged to overcome challenges posed by intense competition and shifting consumer preferences. Recommendations include embracing digital marketing platforms, enhancing production capacity, and innovating product variations and packaging. This study underscores the importance of integrating modern strategies to ensure the sustainability and growth of small businesses in an increasingly dynamic market environment.